Strain Analysis and Kinematics of Deformation of the Tectonic Nappe Pile in Olympos-Ossa Mountainous Area: Implication for the Exhumation History of the HP/LT Ampelakia Unit and the Olympos-Ossa Tectonic Window (Eastern Thessaly, Central Greece) - Ioannis Vrontzos; Emmanouil Katrivanos; Ilias Lazos; Lambrini Papadopoulou; Adamantios Kilias (Geosciences, 2024)
This paper focuses on the structural and finite strain analysis of the Pelagonian nappe, the HP/LT Ampelakia unit, and the Olympos-Ossa unit in the Olympos-Ossa mountainous area in order to better understand the exhumation history of the Ampelakia unit and the underlain Olympos-Ossa unit. Two main stages of Tertiary deformation were revealed, related to nappe stacking and exhumation processes. During the Paleocene–Eocene crustal subduction, HP/LT metamorphism, compression, and nappe stacking were developed progressively. This D1 stage was terminated with the final SW-ward emplacement of the Ampelakia and Pelagonian nappe on the Olympos-Ossa unit during the Eocene–Early Oligocene. The next stage of deformation, D2, was developed during the Oligocene–Miocene following the orogenic nappes stacking. D2 was considered an extensional event, related to metamorphic isothermal decompression, nappes tectonic denudation, crustal uplift, and final exhumation of the Ampelakia unit and the Olympos-Ossa unit as a tectonic window. The calculated finite strain ellipsoids indicate a main flattening type strain geometry and middle strain intensity, increasing along the nappe contacts. The quartz C-axes diagrams also reveal a flattening type of deformation and non-coaxial flow towards the southwest and northeast at the western and eastern flanks of Olympos-Ossa Mountain, respectively. The calculated Wk vorticity number ranges from 0.23 to 0.93.